الرياضة المدرسية في المؤسسات التربوية الجزائرية بين النصوص التشريعية المنظمة وواقع الممارسة - بن شني, فغلو; بلغيث, عبدالقادر ((institut d’éducation sportive et physique / Université de Mostaganem, 2023, 2023)
ملخص الدراسة بالعربية : العنوان الدراسة : "الرياضة المدرسية في المؤسسات التربوية الجزائرية بين النصوص التشريعية المنظمة وواقع الممارسة" هدف الدراسة: التعرف على الواقع الذي تعيشه الرياضة المدرسية من وجهة نظر الأساتذة المنسقين في الجمعيات الثقافية الرياضيةبالمتوسطاتوالثانويات،وكذارؤساءالتعاونياتالثقافيةوالرياضةبالابتدائيات. الفرضية العامة للدراسة: - تراجعمستوىالرياضةالمدرسيةمنحيثالممارسةوالنتائجهومايعكسواقعهاالحالي. عينة الدراسة :- 8 مدراء كرؤساءالتعاونياتالثقافيةوالرياضةبالمرحةالابتدائية -31 أستاذ منسق فيالجمعياتالثقافيةالرياضية بالمرحلة المتوسطة - 9 أساتذة منسقينفيالجمعياتالثقافيةالرياضيةبالمرحلة الثانوية المنهج المتبع في الدراسة : المنهج الوصفي. أدوات الدراسة: الإستبيان نتائج الدراسة : ° هناك معوقات إدارية و تنظيمية تحول دون تجسيد النصوص التشريعية المنظمة للرياضة المدرسية على أرض الواقع . ° هناك مشاكل مادية و تمويلية تقف عقبة في السير الحسن للنشاط الرياضي المدرسي. °هناكإهمالللجمعياتالثقافيةوالرياضيةفيالمؤسساتالتربوية،والتراجعالزائدفيالإهتمامبهارغمكونهاالخليةالأساسيةللرياضةالمدرسية. الاقتراحات الأساسية : * تشكيل لجان مشتركة بين وزارتي التربية الوطنية والشباب والرياضة تقوم على متابعةوتجسيدالنصوصوالقوانينالمتعلقةبالرياضةالمدرسيةعلىأرضالواقعوعدمإبقائهاحبيسةالورق. * الحاجةإلىبرمجةأيامتكوينيةللتعرفوالشرح المعمقللنصوصالتشريعيةالمنظمةللرياضةالمدرسية،وكذاطرقتنظيموتسييرالرياضةالمدرسية. * لزومالإهتمامبالجمعياتالثقافيةوالرياضيةبالمؤسساتالتربوية من قبل القائمين عليهاوضرورة إعادةبعثهاوإعطاءهاالأهميةوالدورالموكللها من قبل المسؤولين على الرياضة المدرسية. * تخصيصأغلفةماليةكافيةوفقالبرامجالمسطرةللنشاطالرياضيالمدرسيوصرفهابشكلكامل. Study summary: The title of the study: "School sports in the Algerian educational institutions between the regulatory texts and the reality of practice." The aim of the study: to identify the reality experienced by school sports from the point of view of coordinating professors in cultural and sports associations in middle and high schools, as well as heads of cultural and sports cooperatives in elementary schools. The general hypothesis of the study: - The decline in the level of school sports in terms of practice and results, which reflects its current reality. The study sample : - 8 managers as heads of cultural and sports cooperatives in the primary stage - 31 professor coordinators in cultural and sports societies in the intermediate stage - 9 professors coordinators in cultural and sports associations at the secondary level The method used in the study: the descriptive method. Study tools: questionnaire and interview Results : ° There are administrative and organizational obstacles that prevent the embodiment of the legislative texts regulating sports training on the ground. ° There are financial and financial problems that stand as an obstacle in the good conduct of school sports activities. ° There is a neglect of cultural and sports associations in educational institutions and the excessive decline in interest in them, despite being the basic cell of school sports.
MEPS-2023-4
Keywords: الرياضة المدرسية - المؤسسات التربوية الجزائرية - النصوص التشريعية - واقع الممارسة